Discovery of the first kimberlitic pipes at Borborema Province, NE Brazil - CABRAL NETO, Izaac (2015)
Two new kimberlitic pipes were discovered in the northern portion of Rio Grande do Norte state during fieldworks developed into the Diamond Brazil Project. The intrusions were named as Santa Fé-1 and Santa Fé-2 and are located in the Rio Piranhas-Seridó domain, Borborema Province. Santa Fé-1 and Santa Fé-2 pipes have areas of 27 ha and 9 ha, respectively, and exhibit a volcaniclastic kimberlite breccia texture containing ilmenite, garnet, spinel and clinopyroxene in abundance. Eclogite garnet contains Na2O > 0.07 wt. % and has been classified as G3"D" and G4"D". According to ground magnetic and gravity survey data, the kimberlitic intrusions are cylindrical bodies, magnetically stratified and discordantly hosted into highly magnetic and dense rocks, which correspond to granodioritic and tonalitic orthogneisses and migmatites of the Arabia Complex (2546 ± 4.2 Ma, SHRIMP U-Pb zircon). The recognition of kimberlitic pipes with expressive dimensions in an off-craton setting opens new horizons to the exploration of primary sources for diamonds in the Borborema Province and especially in the Rio Grande do Norte state.